Lower Risk of Recurrence After Mesh Repair Versus Non-Mesh Sutured Repair in Open Umbilical Hernia Repair: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. (September 2019) - Bisgaard, T.; Kaufmann, R.; Christoffersen, M. W.; Strandfelt, P.; Gluud, L. L.
Background and Aims: The use of mesh repair in a small- or middle-sized umbilical hernia remains controversial, and evidence is based on only few and small heterogeneous randomized trials. The primary aim was to assess differences, if any, in recurrence (clinical and reoperation), and secondary aim was to assess differences in infections, seroma formation, hematomas, chronic pain, cosmetic result, and quality of life. Method: A systematic review (predefined search strategy) and meta-analyses were conducted based on pre-study strict and well-defined methodology. The literature search was completed on 1 January 2018. The study protocol was registered in PROSPERO. Results: Five randomized controlled trials were identified (mesh repair, n = 326 versus non-mesh sutured repair, n = 330) and 602 records were excluded. Randomized controlled trials included patients with defect diameters of ⩾1 to 4 cm. Mesh repair reduced the risk of recurrence compared with sutured repair with a relative risk of 0.28 (95% confidence interval = 0.13–0.58, I 2 = 0%, number needed to treat = 13 patients). Additional analyses found no differences between the two surgical techniques regarding infection (relative risk = 0.80, 95% confidence interval = 0.36–1.79), seroma formation (relative risk = 1.38, 95% confidence interval = 0.57–3.32), or hematomas (relative risk = 0.55, 95% confidence interval = 0.23–1.30). Lack of sufficient data precluded meta-analysis evaluating risk of seroma formation, hematomas, chronic pain, cosmetic result, and quality of life. Conclusion: Mesh repair is recommended for umbilical hernia of ⩾1 to 4 cm. More evidence is needed for the optimal placement of the mesh (sublay or onlay) and the role of mesh in patients with an umbilical hernia <1 cm.